Acute resistance exercise training does not augment mitochondrial remodelling in master athletes or untrained older adults - Marshall, Ryan Neil; McKendry, James; Smeuninx, Benoit; Seabright, Alex Peter; Morgan, Paul T.; Greig, Carolyn; Breen, Leigh (Frontiers in Physiology, 2023)
Background: Ageing is associated with alterations to skeletal muscle oxidative metabolism that may be influenced by physical activity status, although the mechanisms underlying these changes have not been unraveled. Similarly, the effect of resistance exercise training (RET) on skeletal muscle mitochondrial regulation is unclear. Methods: Endurance-trained masters athletes ([MA],74 ± 3 yrs) and untrained older adults ([OC]. 69 ± 6 yrs) completed a single session of knee extension RET (6 x 12 repetitions, 75% 1-RM, 120-second intra-set recovery). Vastus lateralis muscle biopsies were collected pre-RET, 1hr post-RET, and 48hr post-RET. Skeletal muscle biopsies were analyzed for citrate synthase (CS) enzyme activity, mitochondrial content, and markers of mitochondrial quality control via immunoblotting. Results: Pre-RET CS activity and protein content were ~45% (P<0.001) and ~74% greater in MA compared with OC (P=0.006). There was a significant reduction (~18%) in CS activity 48hr post-RET (P<0.05) in OC, but not MA. Pre-RET abundance of individual and combined mitochondrial electron transport chain (ETC) complexes I-V were significantly greater in MA compared with OC, as were markers of mitochondrial fission and fusion dynamics (p-DRP-1Ser616, p-MFFSer146, OPA-1 & FIS-1, P<0.05 for all). Moreover, MA displayed greater expression of p-AMPKThr172, PGC1, TFAM and SIRT-3 (P<0.05 for all). Notably, RET did not alter the expression of any marker of mitochondrial content, biogenesis, or quality control in both OC and MA. Conclusion: The present data suggest that long-term aerobic exercise training supports superior skeletal muscle mitochondrial density and protein content into later life, which may be regulated by greater mitochondrial quality control mechanisms and supported via superior fission-fusion dynamics. However, a single session of RET is unable to induce mitochondrial remodelling in the acute (1hr post-RET) and delayed (48hr post-RET) recovery period in OC and MA.